2000
DOI: 10.3233/jad-2000-2103
|View full text |Cite
|
Sign up to set email alerts
|

Brain Iron and Zinc Contents of German Patients with Alzheimer Disease

Abstract: Our first project aimed to determine the average values of Fe and Zn in normal German human brain (5 individuals, 10 brain parts). Determinations were carried out by instrumental neutron activation analysis in Berlin. Quality control measurements were performed using National Institute of Standard Technology standard reference materials. The present results show non-homogeneous distribution of Fe and Zn in normal human brain. Our second goal was to study the possible elemental concentration changes in German p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Several studies have shown an increase in zinc in AD neocortex [7, 13, 61, 62] while others have found no significant increase [11, 63] and two have found a decrease in zinc [8, 64]. Our result demonstrates that zinc is increased in AD only in grey matter.…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have shown an increase in zinc in AD neocortex [7, 13, 61, 62] while others have found no significant increase [11, 63] and two have found a decrease in zinc [8, 64]. Our result demonstrates that zinc is increased in AD only in grey matter.…”
Section: Discussionsupporting
confidence: 56%
“…From our data (Table 3) it can be seen that corresponding regions from the two hemispheres of three human brains revealed similar concentrations in general, which is in accordance with other essential element studies [26,27]. Interestingly, in certain cases (e.g.…”
Section: Resultssupporting
confidence: 90%
“…NIST 1571 Orchard leaves b 160±20 [16] 175±6 173±4 [29] 177±8 [30] remained in brain tissue [26]. The present finding indicates the high lipid solubility of iodine and its complexes.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Normal processing of APP by α-secretase cleavage in the Golgi complex leads to formation of sAPP, a neurotrophic factor [198]. Additional proteolytic processing of APP by β-secretase (BACE) at the β-cleavage site [5,31,94,171,189] occurs in endosomes [107,115], where acidic pH necessary for β-secretase activity is possible [198]. Further processing by the γ-secretase complex at the plasma membrane (reviewed [172]) leads to formation of Aβ, a 40 or 42 amino acid peptide that is the major component of SP in AD [168].…”
Section: Zinc and Amyloid Beta (Aβ) Peptide Processing And Aggregationmentioning
confidence: 99%